Accounting for managers (Vikas Publishing House, 2013)
It provides students with the knowledge of basic accounting principles and practices in a systematic manner. the book has been presented in a simple way which enable students to understand the subjects and solve practical problems with ease. The main strength of the books are plentiful illustrative examples and the end of chapter exercise with answers